Do specific entrepreneurial ecosystems favor high-level networking while others not? Lessons from the Hungarian IT sector - Komlósi, Éva; Sebestyén, Tamás; Tóth-Pajor, Ákos; Bedő, Zsolt (PTE KTK Műhelytanulmányok, 2021)
Each territorial unit is characterized by a specific entrepreneurial ecosystem (EE) consisting of interdependent actors and contextual factors that support or limit entrepreneurial innovation. Access to and mobilization of entrepreneurial resources is facilitated by social networks within the entrepreneurial ecosystem. However, the degree and quality of these networks is determined by various characteristics of the particular ecosystem itself. Using fuzzy-set Qualitative Comparative Analysis (fsQCA), we explored the configurations of micro, meso and macro conditions of the entrepreneurial ecosystem of ICT firms in a Hungarian city (Pécs), which result in a high or very high-level networking performance. Our results show that certain ecosystems are capable of high-quality networking. In addition, we find that different ecosystem configurations are required for high informal, formal, or external networks.